Manajemen Hubungan Masyarakat dalam Membangun Sekolah Unggulan di Sekolah Dasar Islam Terpadu Sabilul Huda Cirebon - Asep Kurniawan (JIEM (Journal of Islamic Education Management), 2023)
The existence of public relations in schools plays an important role as a communication liaison and building partnerships between schools and their communities to create superior schools. The purpose of this study was to reveal in-depth the management of public relations in building excellent schools in Islamic Primary Full Day School Sabilul Huda. This research was a descriptive qualitative field research. Data collection instruments were in-depth interviews, in-depth observation, and documentation. The analysis technique was done through data reduction, data display, and data inference. The results showed that the management of public relations was implemented by Primary Islamic Full Day School Sabilul Huda could be categorized as successful in building superior schools. It was shown from the academic achievements of student learning outcomes and non-academic achievements of the development of students' interests and talents. This public relations management was carried out through planning, implementation, and evaluation. Public Relations had a role in guarding the implementation of these programs and were responsible to the principal. The awareness of all parties in optimizing these programs was in accordance with their fields and abilities in realizing the excellence of schools.